Pengaruh Brand Association, Brand Awareness, dan Brand Loyalty terhadap Brand Equity: (Studi Konsumen Smartphone Samsung pada Generasi Z di Kota Nias) - Sernide Zebua; Agus Sriyanto (Jurnal Riset dan Inovasi Manajemen, 2025)
This study aims to determine the effect of brand association, brand awareness, and brand loyalty on brand equity. The background of this research is the increasing competition in the smartphone industry, where leading brands are competing to capture consumer attention, particularly Generation Z, who have unique characteristics in using technology. Generation Z is a group that is highly engaged with digital development, quick in accessing information, and critical in making brand choices. Therefore, understanding the factors that influence brand equity among this generation is essential, especially for Samsung as the research object. This research is categorized as quantitative with a descriptive-verificative approach. The population in this study consisted of Samsung smartphone consumers from Generation Z in Nias City. Data were collected using questionnaires designed to measure the independent variables, namely brand association, brand awareness, and brand loyalty, as well as the dependent variable, brand equity. The sampling technique applied was non-probability sampling with a purposive sampling approach, where respondents were selected based on specific criteria. The total sample obtained was 100 respondents. The collected data were analyzed using SPSS version 22. The analysis was conducted to examine the partial effect of each independent variable on the dependent variable. The findings indicate that brand association, brand awareness, and brand loyalty each have a significant partial effect on brand equity. These results suggest that the stronger the brand associations held by consumers, the higher their awareness of Samsung as a brand, and the greater their loyalty, the stronger the brand equity will be among Generation Z. The implications of this study highlight the importance for companies to strengthen brand-based marketing strategies by emphasizing emotional value, enhancing brand exposure, and maintaining consumer loyalty. Such efforts will enable Samsung to sustain its competitive position in the increasingly dynamic smartphone market.